2022
DOI: 10.1108/jiabr-03-2022-0061
|View full text |Cite
|
Sign up to set email alerts
|

Relative financial deprivation, financial anxiety and financial satisfaction: the role of access to Islamic financing among MSME owners amidst COVID-19

Abstract: Purpose The purpose of this paper is to augment the present literature on the relationship between relative financial deprivation (RFD), financial anxiety (FA), access to Islamic financing (AIF) and financial satisfaction (FS) of micro, small and medium enterprise (MSME) owners. Principally, the study examines the moderating role of AIF on the RFD–FS and FA–FS relationships. Design/methodology/approach Quantitative survey approach was used to collect data through self-administered questionnaires from MSME ow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
(100 reference statements)
0
7
0
Order By: Relevance
“…On a sample of 427, the single factor extraction was 39.69%, below the recommended value of 50%, indicating no CMB problem in the present model (Rahman et al. , 2021; Mahmoud et al. , 2022).…”
Section: Data Analysis and Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…On a sample of 427, the single factor extraction was 39.69%, below the recommended value of 50%, indicating no CMB problem in the present model (Rahman et al. , 2021; Mahmoud et al. , 2022).…”
Section: Data Analysis and Resultsmentioning
confidence: 53%
“…The present article analyzes the significance of FIS in the context of individuals and examines how they are affected by financial crises. Earlier research by Mahmoud et al (2022) confirmed that relative financial deprivation and anxiety affect FIS. However, no study has been directed to the financial attitude (FA), financial self-efficacy (FSE), financial knowledge (FK), financial stress (FS) and demographic characteristics (DC) influences on FB and FIS.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…One of the functions of Islamic financial institutions is to empower MSMEs (Rokhman & Abduh, 2019). MSMEs have been hampered by access to funding from formal financial institutions (Mahmoud et al, 2022). In order to overcome these obstacles, non-bank financial institutions are increasingly growing and developing in the community that carry out business activities, including business development services and community empowerment.…”
Section: Introductionmentioning
confidence: 99%